Positioning in mathematics: A case of 6-year-old students collaborating on combinatorics - Palmér, Hanna; Ebbelind, Andreas; Danielsson, Kristina; Patron, Emelie; Wernholm, Marina (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
In mathematics education, collaboration between students is often emphasised as something desirable. The focus of this paper is on positioning in mathematics during collaborative problem solving and problem posing while exploring combinatorics. The study utilises the Learning Design Sequence model for lesson design and positioning theory as an analytical framework. In a sequence of lessons, students worked with both problem solving and problem posing, using different ways of representing their solutions, such as pictures, physical objects, and digital animations. One case of two 6-year-old students is used to illustrate their positioning during this sequence of lessons. One conclusion is that, when collaborating, students’ views of each other as learners in general and mathematics learners in particular may hinder the process of meaning making in mathematics.